The Emerging Role of Poly (ADP-Ribose) Polymerase Inhibitors as Effective Therapeutic Agents in Renal Cell Carcinoma - Pletcher, Jerred P.; Bhattacharjee, Sayani; Doan, Jonathan P.; Wynn, Rebecca; Sindhwani, Puneet; Nadiminty, Nagalakshmi; Petros, Firas G. (Frontiers in Oncology, 2021)
Renal cell carcinoma (RCC) is the sixth most common cancer in the US. However, no significant changes in management have occurred since the tyrosine kinase era until the recent breakthrough with checkpoint inhibitors. Therefore, the need for more therapeutic options is paramount. Our objective was to determine whether PARP inhibition represents a novel therapeutic option for RCC. We used publicly available COSMIC, GDC Data Portal, and cBioPortal databases to explore mutations in DNA repair genes in RCC tissues from the TCGA cohort. We treated a human normal renal epithelial cell line RPTEC/TERT1 and two human renal cancer cell lines ACHN and CAKI-2 with PARPi niraparib, olaparib, rucaparib, veliparib, and talazoparib. Cell survival, cell proliferation, clonogenic ability, and apoptosis were assessed. RCC xenografts in SCID mice were treated with PARPi to evaluate their efficacy in vivo. Data mining revealed that ~27-32% of RCC tissues contain mutations in homologous recombination genes. Niraparib and talazoparib were the most effective at reducing cell survival, proliferation, and clonogenic ability in vitro. Niraparib, talazoparib, and rucaparib were the most effective in reducing RCC xenograft growth in vivo. Agents such as PARPi that exploit mutations in DNA damage repair genes may be effective therapeutic options for RCC.